Recent progress and perspectives of advanced Ni-based cathodes for aqueous alkaline Zn batteries - Ma, Yanfen; Song, Xin; Hu, Wenjing; Xiong, Jiawei; Chu, Pan; Fan, Yanchen; Zhang, Biao; Zhou, Hongyu; Liu, Chenguang; Zhao, Yi (Frontiers in Chemistry, 2024)
Rechargeable aqueous alkaline Zn-Ni batteries (AZNBs) are considered a potential contender for energy storage fields and portable devices due to their inherent safety, high output voltage, high theoretical capacity and environmental friendliness. Despite the facilitated development of AZNBs by many investigations, its practical application is still restricted by inadequate energy density, sluggish kinetics, and poor stability. Therefore, Ni-based cathodes with boosted redox chemistry and enhanced structural integrity is essential for the high-performance AZNBs. Herein, this review focus on critical bottlenecks and effective design strategies of the representative Ni-based cathode materials. Specifically, nanostructured optimization, defect engineering, ion doping, heterostructure regulation and ligand engineering have been employed from the fundamental aspects for high-energy and long-lifespan Ni-based cathodes. Finally, further exploration in failure mechanism, binder-free battery configurations, practical application scenarios, as well as battery recycling are considered as valuable directions for the future development of advanced AZNBs.